Research Progress of Microorganisms in Pickles and Their Relationship with Flavor and Quality of Products - Tong LI; Rina WU; Qisheng ZHANG; Fangfang WANG; Chunli LIU; Ruixue DING; Danli YAN; Junrui WU (Shipin gongye ke-ji, 2022)
Pickle is a traditional Fermented food in China, which has a history of thousands of years. Pickles have attracted wide attention as a health food in the world because of their unique flavor, quality and probiotics. In recent years, as the next generation of high-throughput sequencing technologies, the third generation sequencing technology, acer genomics and transcriptome study etc are widely used in the study of molecular biology technology in fermented food. Researches on the microbial community diversity and function mechanism in the pickles have made significant progress, however, the relevant generalizations are not comprehensive enough. Therefore, this paper focuses on the relationship between microorganisms in pickles and the formation of flavor substances in recent years, the formation mechanism of flavor substances, summarizes the control and utilization of microorganisms in pickles and other aspects of the latest research progress, and describes the diversity and probiotics of microorganisms in pickles. It is expected to provide reference for further study on the formation mechanism of the flavor substances of pickles, improve the flavor quality of pickles, and realize the modern processing of traditional pickles.